The Effect of Using Financial Information Service System (SLIK) on Bad Credit Rate in Fintech Peer to Peer Lending - Elida Tobing (International Journal of Social Service and Research, 2023)
The development of Fintech Peer to Peer Lending (P2P Lending) in Indonesia is very rapid in supporting increased financial inclusion. Along with the increase in the value of loans disbursed through P2P Lending, the ratio of bad loans or what is often referred to as Non Performing Loans (NPL) also continues to increase. Literature review article "Can the Use of a Financial Information Service System (SLIK) Affect the Level of Bad Credit in Fintech Peer to Peer Lending?" is a scientific article that aims to build a research hypothesis on how one variable influences other variables. The method used in writing this literature review article uses the library research method. The sources used as material for research are through available data from the website of the Otoritas Jasa Keuangan (OJK) & Asosiasi Fintech Pendanaan Bersama Indonesia (AFPI), academic online media, Google Scholar, Mendeley, and other online media. The results of this study provide information that can be used in efforts to minimize the occurrence of an increase in credit risk (NPL) in the P2P Lending industry, namely by taking preventive steps by making an effective creditworthiness assessment to prospective loan recipients through analysis of credit information data obtained from Sistem Layanan Informasi Keuangan (SLIK). Therefore, as an effort to restrain the rate of increase in the number of bad loans in the P2P Lending industry, a tool is needed to carry out an effective credit scoring (credit scoring) by integrating P2P Lending credit loan data into SLIK so that more credit data of prospective loan recipients can be obtained. comprehensive. More comprehensive data can provide more accurate results on credit scoring, and have a positive impact on loan repayment rates.